2021
DOI: 10.3390/agronomy11050865
|View full text |Cite
|
Sign up to set email alerts
|

Confounding Factors in Container-Based Drought Tolerance Assessments in Solanum tuberosum

Abstract: Potato is an important food crop with high water-use-efficiency but low drought tolerance. The bottleneck in drought tolerance breeding is phenotyping in managed field environments. Fundamental research on drought tolerance is predominantly done in container-based test systems in controlled environments. However, the portability of results from these systems to performance under field conditions is debated. Thus, we analyzed the effects of climate conditions, container size, starting material, and substrate on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…The comparison of the DRYMp distribution showed large differences between lines and considerable variation between years. The differences between years may result from insufficient sample size for tolerance assessment in a single experiment (Köhl et al 2021). Based on the data from experiments F3 to F8 (see Table S1), Köhl et al (2021) showed that a minimum of three experiments is required to achieve a stable tolerance assessment.…”
Section: Drought Tolerance Assessment Based On Tuber Starch Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…The comparison of the DRYMp distribution showed large differences between lines and considerable variation between years. The differences between years may result from insufficient sample size for tolerance assessment in a single experiment (Köhl et al 2021). Based on the data from experiments F3 to F8 (see Table S1), Köhl et al (2021) showed that a minimum of three experiments is required to achieve a stable tolerance assessment.…”
Section: Drought Tolerance Assessment Based On Tuber Starch Yieldmentioning
confidence: 99%
“…The differences between years may result from insufficient sample size for tolerance assessment in a single experiment (Köhl et al 2021). Based on the data from experiments F3 to F8 (see Table S1), Köhl et al (2021) showed that a minimum of three experiments is required to achieve a stable tolerance assessment. Therefore, we calculated a general DRYMp for each genotype for the three test environments from the combined data of the three (big-bag, pot) or seven (field) experiments; the distribution of which are shown in Fig.…”
Section: Drought Tolerance Assessment Based On Tuber Starch Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…We acknowledge that plant response in a semi-controlled environment does not necessarily translate to the performance of open-field performance of planted seedlings under drought [ 129 , 130 ], since in other studies, lower growth and photosynthesis rates have been found in potted plants, without changes in biomass ratios among plant parts as compared to open-field transplants [ 131 ]. Thus, our results should be confirmed with field trials where roots have an entire soil profile to develop.…”
Section: Discussionmentioning
confidence: 99%
“…First, in the present study, plants were derived from in vitro cultivation without storage starch from a seed tuber. Because the size of the seed tubers influences the performance of the plants, the comparability of plants from in vitro culture is limited (Köhl et al, 2021). Furthermore, the substrate is an essential factor for drought stress trials (Köhl et al, 2021).…”
Section: Discussionmentioning
confidence: 99%